2012
DOI: 10.1007/s00221-012-3310-6
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of absent visual feedback control on gait variability during different locomotion speeds

Abstract: Healthy persons exhibit relatively small temporal and spatial gait variability when walking unimpeded. In contrast, patients with a sensory deficit (e.g., polyneuropathy) show an increased gait variability that depends on speed and is associated with an increased fall risk. The purpose of this study was to investigate the role of vision in gait stabilization by determining the effects of withdrawing visual information (eyes closed) on gait variability at different locomotion speeds. Ten healthy subjects (32.2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
52
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 33 publications
5
52
1
2
Order By: Relevance
“…In conformance with previous studies, we observed that deprivation of visual feedback resulted in a decrease of dynamic walking stability during slow walking indicated by increased fore-aft (i.e., stride time and stride length) and medio-lateral (i.e., base of support) stride-to-stride fluctuations, a more variable bilateral phase coordination and a less symmetric gait pattern [3]. It is commonly believed that alterations in walking performance due to a loss of vision cannot be fully compensated by somatosensory and vestibular information [21].…”
Section: Influence Of Noise-enhanced Vestibular Input On Dynamic Gaitsupporting
confidence: 89%
See 3 more Smart Citations
“…In conformance with previous studies, we observed that deprivation of visual feedback resulted in a decrease of dynamic walking stability during slow walking indicated by increased fore-aft (i.e., stride time and stride length) and medio-lateral (i.e., base of support) stride-to-stride fluctuations, a more variable bilateral phase coordination and a less symmetric gait pattern [3]. It is commonly believed that alterations in walking performance due to a loss of vision cannot be fully compensated by somatosensory and vestibular information [21].…”
Section: Influence Of Noise-enhanced Vestibular Input On Dynamic Gaitsupporting
confidence: 89%
“…This observation corresponds to the growing evidence of a speed-dependent role of sensory feedback in locomotion control. Accordingly, the impact of a vestibular, visual or somatosensory loss or perturbation decreases with increasing walking speed [3][4][5]12,24]. Functional imaging studies could further confirm that sensory cortex activity is decreased at faster walking modes [13,32].…”
Section: Influence Of Noise-enhanced Vestibular Input On Dynamic Gaitmentioning
confidence: 91%
See 2 more Smart Citations
“…O controle da marcha em todos os níveis do sistema nervoso depende fortemente das informações sensoriais visuais, vestibulares e proprioceptivas, as quais permitem o seu controle antecipatório 1 e adaptativo 2 (WUEHR et al, 2013).…”
Section: Controle Da Marcha Em Humanos 11unclassified